COMPARISON OF DENTAL PLAQUE DETECTION USING VARIOUS WAVELENGTH OF LIGHT EMITTING DIODE (LED) (Analysis based on digital imaging techniques) - Ika Agustini N; Rinaldi Budi Utomo (FKG Unlam, 2018)
Background: Dental plaque indicates the grade of dental hygiene. Bacterial dental plaque will emit reddish fluorescence, when irradiated by compatible rays. Fluorescence is produced by an object that absorbs appropriate light spectrum photons. Advances technology has developed Light Emitting Diode (LED) that can emit visible light with low energy. Objective: The purpose of this research is to observe the wavelength of LED light that can be used as dental plaque detector. Methods: A quasi experimental study was done on 44 maxillary and mandibular central incisor teeth, Muallimin Yogyakarta boarders. Teeth were exposed using LED colour ring lamp with 400nm wavelength (UV), 420nm (violet), and 450nm (blue). Teeth were photographed using DSLR camera. As control, teeth were applied with disclosing agent. Image result observed by determining the reddish dental plaque fluorescence and counting surface with software design by SST-Laboratory, Faculty of Engineering, UGM, based on digital imaging technique. The comparison of fluorescence surface plaque area between UV light detection, violet, and blue by using disclosing agent which had been undertaken. Data were analyzed by using nonparametric Wilcoxon test. Result: Detection using UV LED 400nm showed reddish fluorescent dental plaque surface (25,7632+20,8247), violet 420nm and blue 450nm showed no fluorescence area, and as control group (29,9177 + 22,1266). Nonparametric Wilcoxon test results showed that there were no significant difference between detection of 400nm UV LED and disclosing agent (p> 0.05). Conclusion: The conclusion of this study is the wavelength of the LED light be able to used as a dental plaque detector is UV LED wavelength 400nm.